The method of integration by substitution derives from the chain rule, or composite function rule:

$${dy}/{dx}={dy}/{du}⋅{du}/{dx}$$In an integral of a binomial expression, such as $(ax + b)^n$, it would be possible to first exapnd the expression, and then take the integral with respect to x. However, if the value of $n$ is large, this would become rather tedious and impractical. If the binomial expression is the denominator, it may also be close to impossible to work out the integral with respect to x.

But, do not panic - help is at hand with the substitution method. By replacing the binomial, $ax + b$, by a letter (traditionally $u$), the composite function rule allows us to find the integral of $u$ with respect to $u$ (i.e. $du$), and to ensure this gives the integral with repsect to $x$, we multiply the integral of $u$ by the 'internal' integral of the binomial.

That was a mouthful, so let's do an example:

$∫(3x + 4)^5dx$

First we assign $u = 3x + 4$, and see that ${du}/{dx} = 3$

We *substitute* these values into the original equation:

$∫(3x + 4)^5dx = ∫(u)^5dx$

Now we have something we can't solve: u to the respect of x. So, we need to change the $dx$ to a $du$, by inserting the ${du}/{dx} = 3$. To make sure the equation balances, we can only multiply by 1, so we rearrange the equation to:${{du}/{dx}}/{3} = 1$.

Now we put this little sleight of hand into our equation and see something we *can* integrate:

$∫(u)^5dx = ∫{{du}/{dx}}/{3}u^5dx = ∫{u^5}/{3}du = 1/3∫u^5du = 1/3{u^6}/6 + C = 1/{18}{u^6} + C$

And now we substitute the binomial expression back in so it makes sense, since we invented the $u$:

$∫(3x + 4)^5dx = 1/{18}(3x + 4)^6 + C$

Integration by parts is the counterpart of the product rule for differentiation:

$${d(u⋅v)}/{dx} = {du}/{dx}⋅v + u⋅{dv}/{dx}$$Integrating with respect to x results in:

$∫{d(u⋅v)}/{dx} = ∫({du}/{dx}⋅v + u{dv}/{dx})dx = ∫{du}/{dx}⋅vdx + ∫u{dv}/{dx}dx$ ⇒ $uv = ∫{du}/{dx}⋅vdx + ∫u{dv}/{dx}dx$, or: $$∫u{dv}/{dx}dx = uv - ∫{du}/{dx}vdx$$where $u$ and $v$ are functions of $x$.

Find the integral of $3xe^x$ with respect to x.

Let $u = 3x$ ⇒ ${du}/{dx} = 3$, or $du = 3dx$.

If ${dv}/{dx} = e^x$, then $v = ∫e^xdx = e^x$.

$∫3xe^xdx = uv - ∫v{du}/{dx}dx = 3xe^x - ∫e^x⋅3dx =$

$= 3xe^x - 3e^x + c = 3e^x(x - 1) + c$

Content © Andrew Bone. All rights reserved. Created : February 5, 2015

The most recent article is:

Air Resistance and Terminal Velocity

View this item in the topic:

and many more articles in the subject:

Environmental Science is the most important of all sciences. As the world enters a phase of climate change, unprecedented biodiversity loss, pollution and human population growth, the management of our environment is vital for our futures. Learn about Environmental Science on ScienceLibrary.info.

born 1953

Andrew Wiles is an English mathematician at Oxford University, who achieved international fame for his proof to Fermat's Last Theorem.

Website © contentwizard.ch | Designed by Andrew Bone